Factors that influence technophobia in Chinese older patients with ischemic stroke: a cross-sectional survey - Yao Sun; Ru Zhang; Di Hu; Yuqing Wang; Chun Wen; Hongwen Ma (BMC Geriatrics)
Abstract Background Older patients with ischemic stroke often have a large number of medical needs, technophobia refers to the irrational anxiety and fear of digital technologies such as mobile communication equipment, artificial intelligence and robots, resulting in emotional reactions such as fear and tension, which will lead individuals to avoid using technology. However, the research on these patients’ technophobia and the factors that may lead to it is limited.  Aims This study aimed to investigate the status of technophobia and analyze its influencing factors in Chinese older patients with ischemic stroke. Methods A cross-sectional study was conducted among 204 older patients with ischemic stroke in a tertiary hospital in Tianjin from March 2023 to March 2024. The Technophobia Scale, Electronic Health Literacy Scale (eHEALS), General Self-Efficacy Scale (GSES), and Social Support Rate Scale (SSRS) were used to assess patients’ technophobia, electronic health literacy, self-efficacy, and social support, respectively. A self-designed general information questionnaire was used to collect demographic information and disease-related information. Multiple linear regression analysis was performed to analyze the influencing factors. Results The total score of technophobia in older patients with ischemic stroke was (44.81 ± 10.02). Multiple linear regression analysis showed that education level, monthly income, number of smart devices, electronic health literacy, self-efficacy, and social support were the main influencing factors of technophobia in older patients with ischemic stroke (P < 0.05), which could explain 35.3% of the total variation. Conclusion The level of technophobia of older patients with ischemic stroke deserves attention, suggesting that medical staff can reduce the technophobia of older patients with ischemic stroke according to their sense of self-efficacy, electronic health literacy, and social support, so as to ensure patients’ smooth medical treatment. Clinical Trial Number Not applicable.